The role of biomarkers as a diagnostic tool in some neoplasms of pet animals - Ali, Abdelmoneim A.; Refat, Nahla A.G. Ahmed; Metwally, Mohamed M.M.; Fathi, Ashraf M.; Sobh, Mohammed S. (Journal of Advanced Veterinary Research, 2024)
Cancerous tumors are one of the main problems that cause of deaths in pet animals. The objective of this paper is to describe histopathological features of some neoplastic masses with confirmation using immunohistochemistry in pet animals. Our study was done from May 2022 to August 2023 in Sharkia governorate, Egypt to correctly recognize 7 cases of pet animal neoplasms "5 cases of dogs and 2 queen case" based on histopathological and immunohistochemical findings. The results revealed 2 cases of TVT in Penis with positive expressions for Iba2 and vimentin , 1 Case of Sebaceous adenoma in Hock joint of male dog skin, 1 case of hepatoid carcinoma in perianal glands of male dog with positive immunolabelling for CK7 , 1 case of chondroblastic osteosarcoma in A 4-year old, male, Great Dane dog and 2 cases of queen with mammary gland adenocarcinoma with positive immunoreactivity for HER-2 and other mixed mammary neoplasm accompanied with sarcoma has positive staining for vimentin. It could be concluded that the histopathological evaluations by H&E stain is the backbone method for neoplasms diagnosis and using some biomarkers added a confirmatory tools for these diagnosis.